2021
DOI: 10.5935/1518-0557.20210083
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between anti-Mu¨llerian hormone, age, and number of oocytes: A retrospective study in a Brazilian in vitro fertilization center

Abstract: excluded. The study included women with fertility issues aged 20-50 years submitted to IVF. A total of 733 patients were included. The patients were divided by age into three groups (≤35 years old; 36-39 years old; ≥40 years old).Results: The mean AMH concentration ranged from 2.65 to 1.35 ng/mL and was significantly different between the groups. The mean total number of retrieved oocytes ranged from 9.5 to 5.42 and was significantly different between the groups. The mean number of mature oocytes ranged from 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…Analyzing the whole data, we got the following results: Our data showed that in patients undergoing IVF -PGT-A, some clinical and laboratory characteristics are the same as the general trend in patients treated with IVF without embryo genetic screening: AMH level, AFC, the number of retrieved oocytes and obtained embryos decreased with maternal age [3]. Table 2 indicated that AFC, the level of AMH, the number of oocytes, and embryos all decreased statistically significantly with the increase of the maternal age groups with p < 0.05.…”
Section: Characteristics Of Study Patientsmentioning
confidence: 69%
“…Analyzing the whole data, we got the following results: Our data showed that in patients undergoing IVF -PGT-A, some clinical and laboratory characteristics are the same as the general trend in patients treated with IVF without embryo genetic screening: AMH level, AFC, the number of retrieved oocytes and obtained embryos decreased with maternal age [3]. Table 2 indicated that AFC, the level of AMH, the number of oocytes, and embryos all decreased statistically significantly with the increase of the maternal age groups with p < 0.05.…”
Section: Characteristics Of Study Patientsmentioning
confidence: 69%
“…For instance, studies conducted in the United Kingdom, Korea, and Egypt also reported a decline in AMH levels with increasing age. [18][19][20] The study's strength lies in its large sample size and the multicenter approach, providing comprehensive data from different regions of India (Figure 8). However, certain limitations should be acknowledged, such as the retrospective nature of the study and the study could not address the migrating population.…”
Section: Resultsmentioning
confidence: 99%
“…13 The studies collectively suggest that Indian women, whether seeking infertility treatment or with a history of natural conception, experience a more rapid decline in AMH levels and have signif- Age-related change in AMH in women seeking fertility -a hospital-based study across India icantly lower AMH concentrations compared to Caucasian women 14 This highlights the importance of early AMH testing to assess ovarian reserve in Indian women and emphasizes the need for tailored approaches in fertility management and treatments for this population. [15][16][17] The current literature [18][19][20] lacks sufficient data on the cut-off value of AMH levels in Indian infertile females.…”
Section: Highlights Introductionmentioning
confidence: 99%